2015
DOI: 10.1371/journal.pone.0121936
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Stroke Volume Estimation by Non-Invasive Blood Pressure Monitoring in Hypergravity

Abstract: BackgroundAltitude and gravity changes during aeromedical evacuations induce exacerbated cardiovascular responses in unstable patients. Non-invasive cardiac output monitoring is difficult to perform in this environment with limited access to the patient. We evaluated the feasibility and accuracy of stroke volume estimation by finger photoplethysmography (SVp) in hypergravity.MethodsFinger arterial blood pressure (ABP) waveforms were recorded continuously in ten healthy subjects before, during and after exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Cardiovascular measurements derived from the Nexfin algorithm [based on the Modelflow algorithm ( Truijen et al, 2012 )] showed good correlation with standard methods including traditional blood pressure measurements (e.g., Riva-Rocci/Korotkoff) ( Eeftinck Schattenkerk et al, 2009 ; Martina et al, 2010 ; Martina et al, 2012 ; Truijen et al, 2012 ; Rao et al, 2018 ), transpulmonary thermodilution, Doppler ultrasound, and rebreathing ( Wesseling et al, 1993 ; Harms et al, 1999 ; Bogert et al, 2010 ; Shibata and Levine, 2011 ; Broch et al, 2012 ; van der Spoel et al, 2012 ; Bubenek-Turconi et al, 2013 ). Additional studies demonstrated that SV and CO can be estimated by photoplethysmography during open heart cardiac surgery (which involves large hemodynamics changes beyond nominal conditions) ( Wesseling et al, 1993 ), exercise ( Bartels et al, 2011 ), and during conditions where hydrostatic pressures are altered such as fluid challenges ( Critchley et al, 2014 ), moderate orthostatic stress due to LBNP ( Harms et al, 1999 ; Shibata and Levine, 2011 ; Goswami et al, 2015b ), and exposure to hyper-gravity up to +4 Gz ( Manen et al, 2015 ). However, some authors argue that the Nexfin system is not a satisfactory substitute for transpulmonary thermodilution techniques to monitor critical care patients ( Fischer et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular measurements derived from the Nexfin algorithm [based on the Modelflow algorithm ( Truijen et al, 2012 )] showed good correlation with standard methods including traditional blood pressure measurements (e.g., Riva-Rocci/Korotkoff) ( Eeftinck Schattenkerk et al, 2009 ; Martina et al, 2010 ; Martina et al, 2012 ; Truijen et al, 2012 ; Rao et al, 2018 ), transpulmonary thermodilution, Doppler ultrasound, and rebreathing ( Wesseling et al, 1993 ; Harms et al, 1999 ; Bogert et al, 2010 ; Shibata and Levine, 2011 ; Broch et al, 2012 ; van der Spoel et al, 2012 ; Bubenek-Turconi et al, 2013 ). Additional studies demonstrated that SV and CO can be estimated by photoplethysmography during open heart cardiac surgery (which involves large hemodynamics changes beyond nominal conditions) ( Wesseling et al, 1993 ), exercise ( Bartels et al, 2011 ), and during conditions where hydrostatic pressures are altered such as fluid challenges ( Critchley et al, 2014 ), moderate orthostatic stress due to LBNP ( Harms et al, 1999 ; Shibata and Levine, 2011 ; Goswami et al, 2015b ), and exposure to hyper-gravity up to +4 Gz ( Manen et al, 2015 ). However, some authors argue that the Nexfin system is not a satisfactory substitute for transpulmonary thermodilution techniques to monitor critical care patients ( Fischer et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of downward inertial force can be quantified as gravity (+Gz, also called G force). Hydrostatic pressure produced by G force causes blood to flow toward the lower body region, and hemodynamic parameters are affected in hypergravity environments [2][3][4][5]. If G stress surpasses the tolerance, military aircrew will probably experience visual disturbances and even G-induced loss of consciousness (GLOC) that will extremely threaten the flight safety [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, we determined SV (and by extrapolation CO and TPR) using Modelflow (Wesseling et al, 1993). Accordingly, we expressed values as the change from baseline, a common approach (Hockin et al, 2019;Hockin and Claydon, 2020;Protheroe et al, 2013) that provides similar precision to the gold standard (Bogert and Van Lieshout, 2005;Harms et al, 1999;Pitt et al, 2004;Manen et al, 2015). Further confidence in our data can be gleaned from previous studies utilizing electrical bioimpedance cardiography that observed similar phasic decreases in SV (Smith et al, 1987).…”
Section: Discussionmentioning
confidence: 94%